The Effect of Guidance and Counseling Services on Students’ Academic Performance in Selected Secondary Schools in Kajara County, Ntungamo District. - Nuncy, Twikirize (Kabale University, 2020)
This study investigated the effect of guidance and counseling services on students’ academic performance in secondary schools in Kajara County, Ntungamo District. The study employed a cross sectional survey design where qualitative and quantitative paradigms were used. The study was carried out in six Secondary schools in Kajara County, Ntungamo District. Questionnaires and Interview Guides were used in collecting data. From a total population of 1482, the sample size of 306 respondents was generated which included head teachers, parents, teachers and learners in Kajara County. Findings revealed that educational, vocational and personal-social guidance and counseling services were provided in schools through among others attending workshops and seminars, holding group discussions, assisting students in subject choices which resulted into better grades and reduced failures. However, student’s unwillingness to discuss their problems, lack of privacy, lack of funds to sponsor guest speakers and attend seminars were notable challenges hindering guidance and counseling in schools which resulted into low scores, difficulties in students’ adaptation thus leading to low performance. The school Head teachers in secondary schools should put in place counseling office where privacy is made a priority. This will encourage more students to seek counseling services. It was recommended that funds must be allocated in the budget to finance guidance and counseling services, time must be allocated for counseling in the school time table and guidance and counseling rooms be provided to provide privacy in schools.